Effectiveness of the "whiz kids through fitness program" (2007)
Children who are overweight are at risk to noncommunicable diseases (NCD) in adult life. (A healthy and active lifestyle can help prevent NCD. The "Whiz Kids Through Fitness Program" was initiated purposely to promote some overweight preventive measures among school children.) This study was conducted to assess the effectiveness of the "Whiz Kids Through Fitness Program" based on changes in weight for age, physical activity level, knowledge, and practices of Grades 1-3 children in St. Scholastica's College (SSC) over a period of two years. The intervention included nutrition education and physical activity components which were carried out from 2004 to 2006. The lessons wee taken from a module developed by the Philippine Association for the Study of Overweight and Obesity (PASOO) and incorporated in the Science and Physical Education curriculum of the school. The children were divided into four cohort groups based on school entry. The results showed that there was a decrease in the proportion of children with above normal weight-for-age (within cohorts) for cohort 1 (from 36.2% to 19.6%), cohort 3 (from 20% to 11.1%), and cohort 4 (from 26.2% to 23.4%), across the observation periods, but a decrease of 4.5% was not statistically significant across the different periods. Lack of physical activity was noted from the mean scores of cohort 1 between (at) baseline and endline (from 5.5±3.14 to 3.64±2.21), and also of cohort 2 (from 5.35±3 to 3.49±2.05). The proportion of less active children significantly increased during the second year for cohort 1 (from 68.9% to 97.8%) and for cohort 2 (from 80.0% to 98%). Knowledge scores did not significantly change by period, but practice scores significantly decreased at the second year of the study (from 3.8±2.17 to 2.26±2.26). In conclusion, the intervention did not show statistically significant changes in physical activity level, knowledge, and practice of the children in a period of two years. Anthropometric data are equivocal, but the directional change in the direction of overweight at the endline may suggest that the program promoted weight loss. More studies of longer duration to assess the effect of the program on the different outcome measures are suggested. Likewise, there is a need to examine the implementation of the program and other factors in the home and school environment that may influence the effect of the program. Policies to promote nutrition education and create a supportive environment for a healthy and active lifestyle should be regularly implemented in the school.
Keywords: Obesity in children; Physical fitness for children